Transcriptomic profiling and discovery of key genes involved in adventitious root formation from green cuttings of highbush blueberry (Vaccinium corymbosum L.) - Haishan An; Jiaying Zhang; Fangjie Xu; Shuang Jiang; Xueying Zhang (BMC Plant Biology, 2020)
Abstract Background Propagation of cuttings is frequently used in various plant species, including blueberry, which shows special root characteristics that may hinder adventitious root (AR) formation. AR formation is influenced by various factors, and auxin is considered to play a central role; however, little is known of the related regulatory mechanisms. In this study, a comparative transcriptome analysis of green cuttings treated with or without indole-butyric acid (IBA) was performed via RNA_seq to identify candidate genes associated with IBA-induced AR formation. Results Rooting phenotypes, especially the rooting rate, were significantly promoted by exogenous auxin in the IBA application. Blueberry AR formation was an auxin-induced process, during which adventitious root primordium initiation (rpi) began at 14 days after cutting (DAC), root primordium (rp) was developed at 21 DAC, mature AR was observed at 28 DAC and finally outgrowth from the stem occurred at 35 DAC. Higher IAA levels and lower ABA and zeatin contents might facilitate AR formation and development. A time series transcriptome analysis identified 14,970 differentially expressed genes (DEGs) during AR formation, of which there were 7467 upregulated and 7503 downregulated genes. Of these, approximately 35 candidate DEGs involved in the auxin-induced pathway and AR formation were further identified, including 10 auxin respective genes (ARFs and SAURs), 13 transcription factors (LOB domain-containing protein (LBDs)), 6 auxin transporters (AUX22, LAX3/5 and PIN-like 6 (PIL6s)) and 6 rooting-associated genes (root meristem growth factor 9 (RGF9), lateral root primordium 1 (LRP1s), and dormancy-associated protein homologue 3 (DRMH3)). All these identified DEGs were highly upregulated in certain stages during AR formation, indicating their potential roles in blueberry AR formation. Conclusions The transcriptome profiling results indicated candidate genes or major regulatory factors that influence adventitious root formation in blueberry and provided a comprehensive understanding of the rooting mechanism underlying the auxin-induced AR formation from blueberry green cuttings.